Measuring the impact of e-banking services in the banking reform process in Iraq Comparative study during the period 2012-2017 - Mutlag, Ahmed S.; Salman, Hazzaa D. (Opción, 2019)
The research problem was to identify the impact of the use of electronic banking services on the banking reform processes in Iraq and try to measure this effect. The study aimed to measure the impact of the use of electronic banking services on banking reform in Iraq during the period 2012-2017. The study has reached a set of results, namely, the impact of electronic banking services on banking reform in both Iraq and Egypt. The most e-banking services affecting banking reform in both countries was the value of electronic financial transfers. Egyptian banking services on banking reform is due to the use of electronic banking services recently in the State of Iraq. The study recommended the need to work on the development of Iraqi banks and provide the necessary technological means and requirements to provide electronic banking services, and to provide appropriate training programs for employees, and update the educational programs offered to students specialized in the field of banking.